(untitled) (Journal of the Management Sciences, 2024)
This study focused on the role of MSMES in solving unemployment problems in selected MSMEs firms in Onitsha Metropolis. The objectives were focused on the relationship between medium scale business and job creation in Onitsha Metropolis; secondly, the relationship between small scale business and self –employment and lastly; the relationship that exists between micro enterprise and sustainable employment in selected MSMEs firms in Onitsha Metropolis. This study was anchored on the theory of entrepreneurial drive. The study adopted descriptive survey research design and simple random sampling technique was used to select the MSMEs firms in Onitsha Metropolis, Anambra State. The population of the study is 89 and Taro Yamane formula was used to determine the sample size of 73. Findings revealed that there is significant role of MSMEs in solving the problem of Unemployment in Nigeria by indicating that there is positive relationship between the medium scale business and job creation; secondly, between small scale business and self – employment and lastly, between micro enterprise and sustainable employment. The study concluded that MSMEs reduces the rate of unemployment as it offers employment at various capacities. Therefore, the study recommended that Government authorities and meaning Nigerians should focus on supporting MSMEs at different categories towards job creation in Onitsha Metropolis